Multistage Genesis of the Haerdaban Pb-Zn Deposit, West Tianshan: Constraints From Fluid Inclusions and H-O-S-Pb Isotopes - Xia, Fang; Li, Shun-Da; Chen, Chuan; Gao, Ling-Ling; Zhang, Xue-Bing; Wang, Ke-Yong (Frontiers in Earth Science, 2021)
The Haerdaban Pb-Zn deposit is located on the western edge of the Chinese Western Tianshan Orogen. This deposit consists of stratiform and veined mineralization hosted in Proterozoic carbonaceous and dolomitic limestone. Three metallogenic stages were recognized: early sedimentary exhalative stage (stage 1), intermediate metamorphic remobilization stage (stage 2), and late magmatic-hydrothermal stage (stage 3). Fluid inclusions (FIs) present in stage 1 are liquid-rich aqueous, with homogenization temperatures of 206–246°C and salinities of 5.9–11.6 wt.% NaCl eq. FIs present in stage 2 are also liquid-rich aqueous, with homogenization temperatures of 326–349°C and salinities of 3.4–6.6 wt.% NaCl eq. FIs present in stage 3 include halite-bearing, vapor-rich aqueous, and liquid-rich aqueous FIs. Homogenization temperatures for these FIs span a range of 249–316°C. Halite-bearing, vapor-rich aqueous, and liquid-rich aqueous FIs yield salinities of 33.8–38.9, 2.6–3.5, and 4.2–8.1 wt.% NaCl eq., respectively. Oxygen and hydrogen isotopic data (δ18OH2O = 2.6 to 13.6‰, δDH2O = −94.7 to −40.7‰) indicate that the ore-forming fluids of stages 1-3 are derive from modified seawater, metamorphic water and magmatic-meteoric mixed water, respectively. Sulfur isotopic data (δ34S = 2.1 to 16.3‰) reveal that ore constituents were derived from the combination of marine sulfate and magmatic materials. Lead isotopic data (206Pb/204Pb=17.002–17.552, 207Pb/204Pb=15.502–15.523, 208Pb/204Pb=37.025–37.503) reveal that ore constituents were derived from a mixed crust-mantle source. We propose that the Haerdaban deposit was a Proterozoic sedimentary exhalative deposit overprinted by later metamorphic remobilization and magmatic-hydrothermal mineralization.